Knowledge, Attitude and Practice of Testicular Self-Examination among Male Teachers of Schools in Gaindakot Municipality, Nawalparasi, Nepal - Neupane, Sarmila; Thapa, Dikshaya; Ranabhat, Mina Kumari (Nepalese Journal of Cancer, 2025)
Background: Testicular cancer is an increasingly common form of cancer that often develops silently and is typically diagnosed in its later stages. Performing regular testicular self-examinations is the most effective way to detect it early. The objective of the study is to identify level of knowledge, attitude and practice of testicular self-examination among teachers of schools in Gaindakot Municipality, Nawalparasi, Nepal Methods: A descriptive cross-sectional study was used to assess the knowledge, attitudes, and practices related to testicular self-examination (TSE) among 116 male school teachers . A non-probability purposive sampling technique was used to select a sample with self-administered questionnaires. Data were collected using self-administered questionnaires and analyzed using descriptive and inferential statistics with SPSS version 22. Results: The findings of the study show that 92.2% of participants were aware of testicular cancer, and overall knowledge of testicular self-examination (TSE) was considered good, with 37.9% providing correct responses. However, only 36.2% were familiar with the steps of performing TSE. Attitudes toward TSE were generally positive, with only 3% expressing negative views. Despite this, actual practice of TSE was very low, with only 5.2% reporting they performed it, while 85.3% reported not practicing it at all. Conclusion: The study concluded that while the majority of respondents had good knowledge and a positive attitude toward testicular self-examination (TSE), their actual practice was very poor. This indicates that although teachers were aware of TSE and understood its importance, they were not applying this knowledge in practice, possibly due to various underlying factors. The low rate of TSE practice suggests that teachers are not actively engaged in testicular screening, which may contribute to the late diagnosis of testicular cancer.